Digital Re-distributed Manufacturing (RdM) Studio. - Tiwari, Ashutosh; Turner, Christopher J.; Zaki, Mohamed; Vladimirova, Doroteya; Geibdorfer, Martin (Cranfield University, 2017)
This is one of five reports conducted as part of a feasibility study for the RECODE Network
Keywords: 'Consumer Goods'; EPSRC; 'RECODE Network'; 'Manufacturing Engineering not elsewhere classified'; 'Manufacturing Processes and Technologies (excl. Textiles)'; 'Manufacturing Management'; Re-distributed Manufacturing'